Effects of self defence training for sexual assault prevention in the Air Force - DuVivier, Roxanne S L; Huber, Mary J; Bass, Julian; Couchon, Alfred R; Avila-John, Alan; Taylor, Ryan; Keferl, Joseph E (Scientia Militaria - South African Journal of Military Studies, 2019)
Sexual assault (SA) in the military has become a prominent societal concern. A recently released Department of Defence report on Military Sexual Abuse (MSA) concluded that SA continues to be a significant problem in the Armed Forces. To address this issue, systematic and cultural change including training military personnel on sexual assault and the prevention and protection against SA are needed. A study examining the effectiveness of a week-long workshop using the Gracie Defence Systems (GDS) was conducted. The results suggest that Gracie training designed to empower military personnel to prevent and protect themselves against SA and teach sexual awareness was effective. The overall effects of the training (f2 = .41; large ES) appear to impact underlying constructs including self-efficacy, self-determination, vigilance, and vulnerability. In addition, differences were found between males and females prior to training (f2 = .44) and after training (f2 = .29) as well as differences between those who had prior self-defence training and those that did not (f2 = .35). Recommendations include field testing and validating a measure that adequately examines self-efficacy, self-determination, vigilance, and vulnerability as well as continued efforts to implement SA training throughout the military and improve policies.